Structural Equation Modeling of the Effect of Sport Mental Energy on Athletic Success: The Mediating Role of Cognitive Flexibility in Iraqi Volleyball Players - Mohammed Alawadi, Mohammed Kamil; Meshkati, Zohreh; Kadhim Alkurdi, Raafat Abdulhadi; Serjuei, Zahra; Ahmadi, Pezhman (Health Nexus, 2025)
The present study aimed to examine the structural relationships between sport mental energy, cognitive flexibility, and athletic success among volleyball players. This research employed a descriptive–correlational design of the cross-sectional type. The statistical population consisted of all male volleyball players in Diwaniyah City, Iraq. A sample of 230 participants was selected through convenience sampling. Data were collected using standardized questionnaires measuring sport mental energy, cognitive flexibility, and athletic success. Data analysis was conducted using SPSS version 26 and AMOS version 23 through the structural equation modeling (SEM) approach. The findings indicated that the proposed conceptual model demonstrated a good fit, and all main and sub-hypotheses were supported. The results showed that sport mental energy had a direct and positive effect on athletic success (path coefficient = 0.352, p < 0.001). Cognitive flexibility also exerted a significant direct effect on athletic success (path coefficient = 0.625, p < 0.001). Furthermore, the mediating role of cognitive flexibility in the relationship between mental energy and athletic success was confirmed. Path analysis revealed that the indirect effect of sport mental energy on success through cognitive flexibility was statistically significant (indirect coefficient = 0.364, p = 0.001). Overall, the results of this study highlight the simultaneous importance of psychological resources (mental energy) and cognitive abilities (flexibility) in enhancing athletes’ performance and success. These findings provide useful guidance for coaches and sport psychologists in designing effective educational and psychological interventions.